Analysis of COVID-19 outbreak in Hubei province based on Tencent's location big data - Hua, Lei; Ran, Rong; Li, Tingrou (Frontiers in Public Health, 2023)
The rapid urbanization has gradually strengthened the spatial links between cities, which greatly aggravates the possibility of the spread of an epidemic. The traditional methods lacks in the early and accurate detection of epidemics. This paper takes the Hubei province as the study area and uses the Tencent's location big data to study the spread of COVID-19. Using ArcGIS as a platform, the urban relation intensity, urban centrality, overlay analysis, and correlation analysis were used to measure and analyze the population mobility data of 17 cities in Hubei province. The results show that there is a high similarity in the spatial distribution of urban relation intensity, urban centrality, and the number of infected people,all showing the spatial distribution characteristics of "one large and two small" with Wuhan as the core and Huanggang and Xiaogan as the two wings. The urban centrality of Wuhan is 4 times higher than that of Huanggang and Xiaogan, and the urban relation intensity of Wuhan with Huanggang and Xiaogan are also the 2 highest in the Hubei Province. Meanwhile, in the analysis of the number of infected persons, it was found that the number of infected persons in Wuhan was about 2 times that of these two cities.Through correlation analysis among the urban relation intensity, urban centrality, and the number of infected people, it is found that there is an extremely significant positive correlation among the urban relation intensity, urban centrality, and the number of infected people, with R2 of 0.976 and 0.938, respectively. Based on Tencent’s location big data, this study conducts epidemic spread research with the goal of "epidemic spatial risk classification and prevention and control level selection", so as to make up for the shortcomings in epidemic risk analysis and judgment,which can provide reference for city managers in order to effectively coordinate existing resources, policy formulation and control of the epidemic.